Antifungal Activity of Gliocladium viride against Fusarium oxysporum - Khamdan Khalimi; Ni Wayan Anik Leana (Jurnal Ilmu Pertanian Indonesia, 2025)
Fusarium oxysporum is a cosmopolitan fungal species that can cause wilt disease in various plants. This study aimed to determine the antifungal activity of Gliocladium viride against F. oxysporum and identify the antifungal compound produced by G. viride. An antagonistic test of G. viride against F. oxysporum was carried out in dual culture. The antifungal activity of G. viride extract on the growth of F. oxysporum was determined using the paper disc diffusion method. The results showed that G. viride inhibited the growth of F. oxysporum colonies, with inhibition percentages ranging from 92.93% to 93.92%. The extract has antifungal activity, with the diameter of the inhibition zone formed being categorized as strong inhibition, which ranges from 19.3 mm to 24.5 mm. G. viride extract contains eleven compounds that have antifungal activity, namely cyclopropanecarboxylic acid; 2-nonanone; 2,3-butanediol; 2-heptanone; acetoin; 2,3-dimethylpyrazine; carbamic acid, phenyl esters; pyridine, 2,3,4,5-tetrahydro; 2-furancarboxaldehyde, 5-methyl; caryophyllene; and 1,2, benzenedicarboxylic acid. The results of this study provide information that G. viride can be used as a biological agent to control wilt in banana, vanilla, tomato and chili plants. Keywords: Gliocladium viride, antifungal activity, Fusarium oxysporum